2008
DOI: 10.1586/14737159.8.2.179
|View full text |Cite
|
Sign up to set email alerts
|

KCa3.1: target and marker for cancer, autoimmune disorder and vascular inflammation?

Abstract: KCa3.1 is a calcium-activated intermediate-conductance potassium ion channel. In humans the channel is expressed in several secretory organs and subtypes of hematopoietic cells, but not detected in excitable tissues. The mRNA level for KCa3.1 is upregulated in activated leukocytes, mitogen-induced endothelial cells and vascular smooth muscle cells, and several types of human cancers, suggesting a possible role for the channel in inflammatory and oncology diseases. Several potent and selective KCa3.1 blockers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
71
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 57 publications
2
71
0
Order By: Relevance
“…33 The KCa3.1 potassium channel has been demonstrated to impact the function of macrophages by regulating intracellular Ca 2+ homeostasis. 9 Furthermore, a recent study indicated that intracellular Ca2 + overloading triggers greater macrophage production of inflammatory mediators and promotes classically activated macrophage M1 polarization. 34 In the present study, we found that decreasing STAT-1 phosphorylation underscores the role of blocking KCa3.1 in inhibiting proinflammatory genes expression during macrophage polarization and attenuating plaque instability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 The KCa3.1 potassium channel has been demonstrated to impact the function of macrophages by regulating intracellular Ca 2+ homeostasis. 9 Furthermore, a recent study indicated that intracellular Ca2 + overloading triggers greater macrophage production of inflammatory mediators and promotes classically activated macrophage M1 polarization. 34 In the present study, we found that decreasing STAT-1 phosphorylation underscores the role of blocking KCa3.1 in inhibiting proinflammatory genes expression during macrophage polarization and attenuating plaque instability.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, KCa3.1 is an attractive pharmacological target for use in immunotherapy. [9][10][11] KCa3.1 gating is voltage independent and only requires a small increase in intracellular calcium. Intracellular calcium binds to calmodulin molecules that are constitutively associated with the channel protein and induce channel opening, which results in K + efflux that maintains a negative membrane potential.…”
mentioning
confidence: 99%
“…In the cardiovascular system, vascular endothelial cells express both IK and SK3 channels, which are implicated in the endothelium-derived hyperpolarizing factor-mediated vasodilation (17)(18)(19)(20). The importance of SK/IK channels is demonstrated further by their potential roles in clinical abnormalities (21)(22)(23)(24). SNPs in the SK/IK genes are thought to play a role in cardiovascular abnormalities, such as familial atrial fibrillation (22,25).…”
Section: +mentioning
confidence: 99%
“…The voltage-insensitive calcium-activated K ϩ channel of intermediate conductance KCa3.1 is now emerging as a therapeutic target for a large variety of health disorders such as autoimmune diseases, vascular inflammation, and cancer (1)(2)(3)(4)(5)(6)(7). Increasing evidence also supports a prominent role of KCa3.1 in respiratory diseases such as allergic asthma (8) and airway obstruction coming from tissues remodeling (8,9).…”
mentioning
confidence: 99%
“…1 has not yet been solved. Knowledge of the channel key structural features is, however, essential for a molecular description of drug/channel interactions.…”
mentioning
confidence: 99%